2019
DOI: 10.1002/jor.24332
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional In Vivo Analysis of Malunited Distal Radius Fractures With Restricted Forearm Rotation

Abstract: Malunited distal radius fractures (DRFs) occasionally restrict forearm rotation, but the underlying pathology remains unclear. We aimed to elucidate the mechanism of rotational restriction by retrospective analysis of 23 patients with unilateral malunited DRFs who presented restricted forearm rotation. We conducted computed tomography during forearm rotation on both sides. Three-dimensional (3D) bone surface models of the forearm were created, and 3D deformity of the distal radius, translation of the distal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Nonetheless, a partial relapse of the deformity was observed at the follow-up visits, therefore, a temporary hemiepiphysiodesis of the tibia was planned during the latest visit. On the basis of the analysis of Miyake [16,17], a new 3D parametric simulation (a) was performed to realign the bones, enabling the achievement of a normal range of motion [18,19]. For the rotational analysis, the cutting plane DTM2 and the rotation point PNT2 were defined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a partial relapse of the deformity was observed at the follow-up visits, therefore, a temporary hemiepiphysiodesis of the tibia was planned during the latest visit. On the basis of the analysis of Miyake [16,17], a new 3D parametric simulation (a) was performed to realign the bones, enabling the achievement of a normal range of motion [18,19]. For the rotational analysis, the cutting plane DTM2 and the rotation point PNT2 were defined.…”
Section: Resultsmentioning
confidence: 99%
“…performed to realign the bones, enabling the achievement of a normal range of motion [18,19]. For the rotational analysis, the cutting plane DTM2 and the rotation point PNT2 were defined.…”
Section: Resultsmentioning
confidence: 99%
“…The relative displacement matrix described above was quantified in three directions using the Euler angle method with these coordinate systems. 15,17 Positive and negative sagittal, coronal, and axial angles were defined as extension and flexion, valgus and varus, and pronation and supination, respectively. The location of the deformity was quantified as the percentage of the total length of the bone from the proximal end.…”
Section: D Deformity Analysismentioning
confidence: 99%
“…Wrist joint contact patterns have been reported to reflect pathological conditions 5 . Kawanishi et al reported that the wrist joint contact area of Kienböck’s disease was changed 6 .…”
Section: Introductionmentioning
confidence: 99%